Effects of 24-week prebiotic intervention on self-reported upper respiratory symptoms, gastrointestinal symptoms, and markers of immunity in elite rugby union players - Parker, C.; Hunter, K. A.; Johnson, M. A.; Sharpe, G. R.; Gibson, G. R.; Walton, G. E.; Poveda, C.; Cousins B.; Williams, N. C. (European Journal of Sport Science, 2023)
Objectives Elite rugby union players face numerous physiological and psychological stressors which can increase upper respiratory and gastrointestinal illness risk, and in turn can compromise training and competitive performance. This study aimed to investigate the effect of daily prebiotic supplementation on upper respiratory symptoms, gastrointestinal symptoms, and markers of immune function in elite rugby union players.